Snapshot Study of Whole Genome Sequences of Escherichia coli from Healthy Companion Animals, Livestock, Wildlife, Humans and Food in Italy - Massella, Elisa (Antibiotics (Basel), 2020)
Animals, humans and food are all interconnected sources of antimicrobial resistance (AMR), allowing extensive and rapid exchange of AMR bacteria and genes. Whole genome sequencing (WGS) was used to characterize 279 Escherichia coli isolates obtained from animals (livestock, companion animals, wildlife), food and humans in Italy. E. coli predominantly belonged to commensal phylogroups B1 (46.6%) and A (29%) using the original Clermont criteria. One hundred and thirty-six sequence types (STs) were observed, including different pandemic (ST69, ST95, ST131) and emerging (ST10, ST23, ST58, ST117, ST405, ST648) extraintestinal pathogenic Escherichia coli (ExPEC) lineages. Eight antimicrobial resistance genes (ARGs) and five chromosomal mutations conferring resistance to highest priority critically important antimicrobials (HP-CIAs) were identified (qnrS1, qnrB19, mcr-1, bla(CTX-M1,15,55), bla(CMY-2), gyrA/parC/parE, ampC and pmrB). Twenty-two class 1 integron arrangements in 34 strains were characterized and 11 ARGs were designated as intI1 related gene cassettes (aadA1, aadA2, aadA5, aad23, ant2_Ia, dfrA1, dfrA7, dfrA14, dfrA12, dfrA17, cmlA1). Notably, most intI1 positive strains belonged to rabbit (38%) and poultry (24%) sources. Three rabbit samples carried the mcr-1 colistin resistance gene in association with IS6 family insertion elements. Poultry meat harbored some of the most prominent ExPEC STs, including ST131, ST69, ST10, ST23, and ST117. Wildlife showed a high average number of virulence-associated genes (VAGs) (mean = 10), mostly associated with an ExPEC pathotype and some predominant ExPEC lineages (ST23, ST117, ST648) were identified.